Effectiveness of Dialectical Behavior Therapy on Received Criticism, Event Minimization and Offender Exoneration in Married Women with Borderline Personality Disorder - Ebrahimi , Golnaz; Vadoodi, Elahe; Anasseri, Mehryar (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to determine the effectiveness of Dialectical Behavior Therapy (DBT) on received criticism, event minimization, offender exoneration, and marital instability among married women diagnosed with Borderline Personality Disorder (BPD). Methods and Materials: Using a quasi-experimental design with pre-test and post-test assessments, the study included 20 married women with BPD selected through purposive sampling from a clinical population in Tehran. Participants were randomly assigned to an experimental group (n=10) that underwent ten sessions of DBT and a control group (n=10) that received no intervention. After accounting for dropouts, each group retained nine participants. Standardized tools were used for assessment: the Family Emotional Involvement and Criticism Scale (FEICS), the Acceptance of Domestic Violence Myths Scale, the Marital Instability Index (MIL), and the Borderline Personality Scale. Data were analyzed using Multivariate Analysis of Covariance (MANCOVA) and Univariate ANCOVA. Findings: Statistical analysis indicated a significant difference in post-test scores between the experimental and control groups. DBT significantly reduced perceived criticism (F = 12.108, p = .001, η² = .601), enhanced event minimization (F = 9.943, p = .008, η² = .453), and increased offender exoneration (F = 10.664, p = .004, η² = .513). Post hoc Tukey tests confirmed the significance of these differences at the 99% confidence level. Conclusion: Dialectical Behavior Therapy was shown to be effective in improving emotional and cognitive responses associated with interpersonal conflict and psychological distress in married women with BPD. The intervention significantly decreased received criticism, promoted cognitive reappraisal through event minimization, and supported interpersonal forgiveness, thereby enhancing marital stability.